Whole genome sequencing of Indonesian dengue virus isolates using next-generation sequencing - Benediktus Yohan; Rama Dhenni; Rahma F Hayati; Frilasita Aisyah Yudhaputri; Dionisius Denis; Yanuarni WB Pamai; Anna Matiana Afida; Ingrid A Hutagalung; Sotianingsih Haryanto; Hidayat Trimarsanto; Khin Saw Aye Myint; R. Tedjo Sasmono (Indonesian Journal of Biotechnology, 2018)
Indonesia is a tropical country and hyperendemic for dengue. The disease prevalently affected Indonesian and it caused high morbidity and substantial economic burden. This vector-borne viral disease is caused by infection of dengue viruses (DENVs), which are the member of Flaviviridae family. While most of dengue studies in Indonesia focused on the epidemiology, the clinical aspects, the vectors, and to certain extent the virology, there were still gaps in the DENVs genomic aspects. Considering their high mutation rate, the DENVs were known for their high genetic diversity and it might affect the characteristics of the viruses. Comprehensive DENV genomic data were thus important for many aspects of disease management, including virus surveillance, pathogenesis, diagnostics, antiviral drug design, and vaccine development. We established in this study a method for DENV whole genome sequencing using the advanced Next-Generation Sequencing (NGS) and Nextera XT DNA library preparation kit, coupled with simplified bioinformatic analysis methods. The Indonesian DENVs from four serotypes were isolated from patients’ sera, while library was prepared from enriched templates and sequenced using Illumina NGS. Our study highlighted the potential of a robust NGS method in producing whole genome sequence of DENVs, which would be important for future dengue studies.